Between the urban and the virtual: Cyclo activism and the relations of material and digital space - Lima , Tiago Eloi de; Ramos, Renata Benedetti Mello Nagy (Seven Editora, 2023)
The relationship between physical spatiality and virtual media is affected and transformed by information technology. The Internet, the "backbone" of global communication (Castells, 2002, p. 431), is a transformative tool and also in constant transformation. And in the so-called "Information Age," not only do the transformations happen at a fast pace, but they also move the social gears responsible for the significant changes in society and the cities quickly. And it could not be different since this century was designated as the urban century by the United Nations – UN. Among the changes, according to Castells (2002), are the interactive computer networks that grow exponentially, creating new forms of communication to articulate socially. Mobile devices, such as laptops, cell phones, tablets, and social networks, are instruments that facilitate communication and the action of activism by reaching instantly and simultaneously a large number of Internet users. With these facilities, many activist groups have appropriated these new media to disseminate information, organize and mobilize the population (CASSIANO, 2011). Among the groups of activists who use digital media is the Ciclo activism, an organized movement of cyclists with records of demonstrations since the 1990s, according to the Union of Cyclists of Brazil - UCB. This group, organized horizontally that is, without leaders, defends the use of the bicycle to the detriment of the use of private motorized transport and acts in the field of clashes over the meanings of urban mobility, issues related to urban planning, and socio-environmental problems in cities. With multiple approaches, they are attentive to urban planning, sustainability, and the use of the bicycle as a means of transportation. Thus, with the increasing use of social networks by various groups of society, the problem arises about the political participation of cyclo activism in the informational territory. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-032